Dielectric Resonator Reflectarray Antenna Unit Cells for 5G Applications - Nur Fazreen Sallehuddin; Mohd Haizal Jamaluddin; Muhammad Ramlee Kamarudin; Muhammad Hashim Dahri; Siti Umairah Tajol Anuar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presents an investigation for the performance comparison of three different unit cell configurations operating at 26 GHz for 5G applications. The unit cells are cross shape dielectric resonator, cross microstrip patch and cross hybrid dielectric resonator. Verification of the comparison has been done by simulations using commercial Computer Simulation Technology Microwave Studio (CST MWS). The simulated results for reflection phase, slope variation, reflection loss and 10% bandwidth were analyzed and compared. The results indicate that the optimum configuration to be deployed for the reflectarray’s unit element in order to fulfill the 5G requirements of a wide bandwidth is the cross hybrid DRA. This configuration is a combination of cross DRA with cross microstrip patch as the parasitic element in order to tune the phase and provide a wide phase range with smooth variation slope. Cross hybrid DRA provided a wide phase range of 520° with 0.77 dB loss and 10% bandwidth of 160 MHz.